Exploring the protective effects of calcium-containing carrier against drying-induced cellular injuries of probiotics using single droplet drying technique. (December 2016) - Zheng, Xufeng; Fu, Nan; Huang, Song; Jeantet, Romain; Chen, Xiao Dong
Abstract: Protective carriers that encapsulate probiotics in spray drying could improve the survival ratio of dried cells through different mechanisms. Unveiling the protective mechanism of each carrier will contribute to a rational design of high performance carrier formulation. This study utilized single droplet drying (SDD) technique to investigate the effects of calcium cation in varied carrier formulation. Inactivation histories of Lactobacillus rhamnosus GG (LGG) in different carriers were compared, and cellular injury history of probiotics during droplet drying was studied for the first time. Adding 1 mM CaCl2 to lactose carrier protected cell viability, mitigated cellular injuries, and enhanced regrowth capability as drying progressed, demonstrating the positive effect of Ca 2 + with possible mechanism of stabilizing sub-cellular structures. At later drying stages, cell survival in Lac/Ca carrier was increased by 0.5–1.5 log on selective media compared to lactose carrier. Supplementing calcium-binding agents lowered the protective effect, shortening the initiation of rapid cell inactivation down to 120 s of drying. Adding CaCl2 to trehalose carrier barely improved cell survival, indicating that the protective effect could be influenced by carrier formulation. Pure trehalose carrier exerted excellent protection on LGG, supporting cells to regrow in liquid rich medium even after 180 s of drying. The protection of trehalose may stem from stabilization of sub-cellular structures, which possibly overlap the effect of Ca 2 + . The findings suggested that high performance carrier formulation might be developed by combining carrier materials with different protective mechanisms, for maximizing the survival of active dry probiotics in industrial spray drying operation. Graphical abstract: Highlights: The injury history of a probiotics strain was studied as droplet drying progressed. Adding Ca 2 + protected cell viability and cellular structures in lactose carrier. The protection was lost upon addition of a chelating agent, e.g. dipicolinic acid. Trehalose well stabilized cellular structures regardless of the addition of Ca 2 + . Carrier formulation is crucial to maximizing protection for drying of probiotics.